MENINJAU KEMBALI INOVASI DAN HAKIKAT PEMBELAJARAN AKIDAH AKHLAK - Dinda Marlina; Septi Anawati; Sukidal, Nindia (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2022)
Learning innovation starts from the result of thinking about the existence of the old paradigm to the new paradigm and is considered to be able to solve problems or be able to improve educational practice. Moral aqidah learning is learning that emphasizes students to have confidence about their identity so that they have good personality and character and stay away from negative and bad things. E-learning is a learning procedure developed for learning activities in today's era. Educators and students are required to be able to adapt to these activities. Although learning is carried out online or remotely, this will not create a gap in teaching and learning activities.